Dipstick proteinuria is an independent predictor of high on treatment platelet reactivity in patients on clopidogrel, but not aspirin, admitted for major adverse cardiovascular events. (3rd October 2015) - Davila, Carlos D.; Vargas, Fernando; Huang, Kuan-Hsiang Gary; Monaco, Thomas; Dimou, Anastasios; Rangaswami, Janani; Figueredo, Vincent M.
Abstract: The effectiveness of aspirin and clopidogrel in patients with chronic kidney disease (CKD) suffering from acute cardiovascular events is unclear. High on treatment platelet reactivity (HTPR) has been associated with worse outcomes. Here, we assessed the association of dipstick proteinuria (DP) and renal function on HTPR and clinical outcomes. Retrospective cohort analysis of 261 consecutive, non-dialysis patients admitted for Major Adverse Cardiovascular Events (MACE) that had VerifyNow P2Y12 and VerifyNow Aspirin assays performed. HTPR was defined as P2Y12 reactivity unit (PRU) > 208 for clopidogrel and aspirin reaction units (ARU) > 550 for aspirin. Renal function was classified based on the estimated glomerular filtration rate (eGFR), and dipstick proteinuria was defined as ≥30 mg/dl of albumin detected on a spot analysis. All cause mortality, readmissions, and cardiac catheterizations were reviewed over 520 days. In patients on clopidogrel ( n = 106), DP was associated with HTPR, independent of eGFR, diabetes mellitus, smoking or use of proton pump inhibitor (AOR = 4.76, p = 0.03). In patients with acute coronary syndromes, HTPR was associated with more cardiac catheterizations ( p = 0.009) and readmissions ( p = 0.032), but no differences in in-stent thrombosis or re-stenosis were noted in this cohort. In patients on aspirin ( n = 155), no associations were seen between DP and HTPR. However, all cause mortality was significantly higher with HTPR in this group ( p = 0.038). In this cohort, DP is an independent predictor of HTPR in patients on clopidogrel, but not aspirin, admitted to the hospital for MACE.